Growth hormone, insulin, and prolactin secretion in anorexia nervosa and obesity during bromocriptine treatment. Issue 6080 (16th July 1977) - Harrower, A D; Yap, P L; Nairn, I M; Walton, H J; Strong, J A; Craig, A
Abstract : We studied secretion of growth hormone (GH), insulin, and prolactin in eight women with anorexia nervosa and nine women with refractory obesity before and during treatment with bromocriptine, 10 mg/day. In the anorexic patients the raised plasma GH concentrations occurring during an oral glucose tolerance test fell significantly while on bromocriptine treatment, but there was no change in plasma insulin or blood glucose concentrations. In the obese patients, however, plasma GH concentrations remained low during the oral glucose tolerance test, and were not modified by bromocriptine. Blood glucose and plasma insulin concentrations were also unchanged. Plasma GH and plasma 11-hydroxycorticosteroid responses to insulin-induced hypoglycaemia were unaffected. Serum prolactin concentrations which were raised in five anorexic patients and marginally raised in two obese subjects, fell significantly in both groups during treatment. We observed no consistent weight changes in either groups.